Development of SEDDS formulation containing caffeine for dermal delivery. (14th March 2023) - de Almeida, Igor de Andrade Assunção; Honório, Thiago da Silva; do Carmo, Flavia Almada; de Freitas, Zaida Maria Faria; Simon, Alice; Rangel Rodrigues, Carlos; Pereira de Sousa, Valeria; Cabral, Lucio Mendes; de Abreu, Letícia Coli Louvisse
Abstract: Objective: The objective of this work was to develop a self‐emulsifying drug delivery system (SEDDS) containing caffeine for the treatment of cellulite. Methods: SEDDS were prepared using the solution method. 0.5% (w/v) caffeine was added to the previously selected excipients. The system was characterized by droplet size, zeta potential, emulsification time and long‐term stability. In vitro release and skin permeation were investigated using Franz‐type diffusion cells. The cytotoxicity was evaluated on normal human keratinocytes. Results: Caffeine SEDDS were thermodynamically stable, with a zeta potential less than ‐ 22 mV and droplet size around 30 nm, and were long‐term stable. The permeation study showed that the formulation promoted caffeine accumulation in the skin layers, suggesting an increase in local circulation. Cytotoxicity studies on HaCaT cells were not conclusive as the surfactant used indicated false‐positive results due to its high molar mass. Conclusion: It was possible to obtain a stable SEDDS that could cause an increase in blood flow in the applied area, resulting in cellulite reduction. Abstrait: Objectif: L'objectif de ce travail était de développer un système d'administration de médicaments auto‐émulsifiants (SEDDS) contenant de la caféine pour le traitement de la cellulite. Méthodes: Les SEDDS ont été préparés par la méthode en solution. 0, 5 % (p/v) de caféine a été ajouté aux excipients préalablement sélectionnés. Le système a été caractérisé par la taille des gouttelettes, le potentiel zêta, le temps d'émulsification et la stabilité à long terme. La libération in vitro et la perméation cutanée ont été étudiées dans des cellules de diffusion de type Franz. La cytotoxicité était évaluée sur des kératinocytes humains normaux. Résultats: Les SEDDS de caféine étaient thermodynamiquement stables, avec un potentiel Zeta inférieur à ‐22 mV et une taille de gouttelettes d'environ 30 nm, et stables à long terme. L'étude de perméation a montré que les formulations favorisent l'accumulation de caféine dans les couches de la peau, suggérant une augmentation de la circulation locale. Les études de cytotoxicité sur les cellules HaCaT n'ont pas été concluantes car le surfactant utilisé indique des résultats faussement positifs dus à une masse molaire élevée. Conclusion: Il a été possible d'obtenir un SEDDS stable qui peut provoquer une augmentation du flux sanguin dans la zone appliquée, entraînant une réduction de la cellulite. Abstract : A SEDDS formulation of caffeine was developed with a reduced droplet size and great accumulation in the dermis, favouring its action in the reduction of cellulite.